Students' Perceptions: Using Writing Process Approach in EFL Writing Class - Utami Dewi (AL-ISHLAH: Jurnal Pendidikan, 2021)
The writing process approach (WPA) is a way to solve the problems of how the students express their ideas in producing essays systematically. The use of WPA needs to be examined from the students' perceptions because students' perception of the use of WPA influences students' writing ability. This study aims to investigate the students' perceptions on the application of WPA in EFL writing classes. This study applied a qualitative approach using a questionnaire and semi-structured interview with a written list of questions as a guide which focused on students' perceptions in the application of the WPA in their writing class. The data of the interview was analyzed by qualitative by using content analysis. The questionnaire results showed that most students had a highly positive and positive perception, while no students had a negative perception of the application of WPA based on the percentages. The results of interviews were concluded in four themes. Firstly, most students reported that they have highly positive opinions on WPA and considered the planning. Secondly, peer feedback is revising strategies as most useful. Thirdly, they stated that the steps in WPA were specific, systematic, and helpful. Lastly, they perceived that their writing product had improved after the application of WPA in writing class. The findings from the interviews corresponded with the findings from the questionnaire, which revealed that students had positive perceptions on the application of WPA in writing class; therefore, WPA can be suggested as the alternative approach to improve students' writing ability.